The illustrated encyclopedia of Catholicism : a comprehensive guide to the history, philosophy and practice of Catholic Christianity, with more than 500 beautiful illustrations - Creighton-Jobe, Ronald (London : Lorenz Books, 2009)
"With its spiritual, cultural and historical heritage, spanning more than 2,000 years, the Catholic religion is formidiably influential across the globe and has a special place in the hearts and minds of millions, This wide-ranging book discusses the history, doctrine and practices of the Catholic religion".
Includes index.
Keywords: Catholic Church -- Encyclopedias; Catholic Church; Encyclopedias